READING ENHANCEMENT THROUGH RECIPROCAL TEACHING TECHNIQUE - Dr. N. Anuradha, Dr. K.Leelavathi, G.Bharathi, (Journal of Computational Analysis and Applications (JoCAAA), 2024)
Reading comprehension is a foundational skill that directly influences learners’ academicsuccess. Reciprocal teaching technique has emerged as an effective instructional strategy that enhances students